DIRECCIONALITY OF VISUAL INFORMATION PROCESSING: A REVIEW FROM THE COGNITIVE POINT OF VIEW - Arnau Gras, Jaume; Blanca Mena, María José; Rosel Remírez, Jesús; Salvador Beltrán, F. (Anales de Psicología / Annals of Psychology)
Navon (1977) found that the global features of a visual form were analyzed more rapidly than the local ones. This was known as "global precedence hyphotesis". An investigation line has been developed with the intention of finding out the veracity of the hyphotesis. The aim of this paper is to realize a theoretical review of this investigation line. On the one hand, it has been suggested that global precedence depends on the stimulus size, number of local elements, quality of information, task, exposure time, presence of noise in the experimental session and localization of the stimulus in the visual field. On the other hand, it has been proposed different alternatives in order to explain this phenomenon: perceptual explanation and attentional explanation.